In-Mold-Assembly of Hybrid Bending Structures by Compression Molding - Stallmeister, Tim; Tröster, Thomas (Key Engineering Materials)
The further development of in-mold-assembly (IMA) technologies for structural hybrid components is of great importance for increasing the economic efficiency and thus the application potential. This paper presents an innovative IMA process concept for the manufacturing of bending loaded hybrid components consisting of two outer metal belts and an inner core structure made of glass mat reinforced thermoplastic (GMT). In this process, the core structure, which is provided with stiffening ribs and functional elements, is formed and joined to two metal belts in one single step. For experimental validation of the concept, the development of a prototypic molding tool and the manufacturing of hybrid beams including process parameters are described. Three-point bending tests and optical measurement technologies are used to characterize the failure behavior and mechanical properties of the produced hybrid beams. It was found that the innovative IMA process enables the manufacturing of hybrid components with high energy absorption and low weight in one step. The mass-specific energy absorption is increased by 693 % compared to pure GMT beams.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

A comparison of heuristic, statistical, and machine learning methods for heated tool butt welding of two different materials - Gevers, Karina; Tornede, Alexander; Wever, Marcel Dominik; Schöppner, Volker; Hüllermeier, Eyke (Welding in the World)
Abstract Heated tool butt welding is a method often used for joining thermoplastics, especially when the components are made out of different materials. The quality of the connection between the components crucially depends on a suitable choice of the parameters of the welding process, such as heating time, temperature, and the precise way how the parts are then welded. Moreover, when different materials are to be joined, the parameter values need to be tailored to the specifics of the respective material. To this end, in this paper, three approaches to tailor the parameter values to optimize the quality of the connection are compared: a heuristic by Potente, statistical experimental design, and Bayesian optimization. With the suitability for practice in mind, a series of experiments are carried out with these approaches, and their capabilities of proposing well-performing parameter values are investigated. As a result, Bayesian optimization is found to yield peak performance, but the costs for optimization are substantial. In contrast, the Potente heuristic does not require any experimentation and recommends parameter values with competitive quality.
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Fingerprints Indicating Superior Properties of Internal Interfaces in Cu(In,Ga)Se 2 Thin‐Film Solar Cells - Raghuwanshi, Mohit; Chugh, Manjusha; Sozzi, Giovanna; Kanevce, Ana; Kühne, Thomas; Mirhosseini, Hossein; Wuerz, Roland; Cojocaru‐Mirédin, Oana (Advanced Materials)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Corrosion Phenomena and Fatigue Behavior of Clinched Joints: Numerical and Experimental Investigations - Harzheim, Sven; Ewenz, Lars; Zimmermann, Martina; Wallmersperger, Thomas (Journal of Advanced Joining Processes)
Lightweight construction has increasingly become the focus of scientific research in recent years, not least due to the constantly increasing fuel price, which is a key factor in the economic viability of many companies. In this respect, the use of hybrid structures, made of dissimilar materials offers many advantages. However, such hybrid structures often have undesirable side effects. For example, brittle intermetallic phases are formed when aluminum and steel are welded. Clinching as a mechanical joining process does not produce such intermetallic phases since the connection is realized through form and force closure. In this process, a punch passes through two or more sheets and forms them into a permanent joint in a die. In the present work, the corrosion phenomena of an aluminum-steel clinched joint have been investigated by both experiments and numerical simulations in order to explain the superior fatigue behavior of pre-corroded joints. Therefore, the clinched joints have been corroded by a three-week salt-spray test. In addition, the electric potential and the von Mises stress are calculated under the assumption of a static loading. The results of both experiments and numerical simulations can explain the improvement in the fatigue behavior of the corroded specimens. This phenomenon can be attributed to the accumulation of corrosion products in small gaps between the joined metal sheets.
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Robustness Analysis of Pin Joining - Römisch, David; Zirngibl, Christoph; Schleich, Benjamin; Wartzack, Sandro; Merklein, Marion (Journal of Manufacturing and Materials Processing)
The trend towards lightweight design, driven by increasingly stringent emission targets, poses challenges to conventional joining processes due to the different mechanical properties of the joining partners used to manufacture multi-material systems. For this reason, new versatile joining processes are in demand for joining dissimilar materials. In this regard, pin joining with cold extruded pin structures is a relatively new, two-stage joining process for joining materials such as high-strength steel and aluminium as well as steel and fibre-reinforced plastic to multi-material systems, without the need for auxiliary elements. Due to the novelty of the process, there are currently only a few studies on the robustness of this joining process available. Thus, limited statements on the stability of the joining process considering uncertain process conditions, such as varying material properties or friction values, can be provided. Motivated by this, the presented work investigates the influence of different uncertain process parameters on the pin extrusion as well as on the joining process itself, carrying out a systematic robustness analysis. Therefore, the methodical approach covers the complete process chain of pin joining, including the load-bearing capacity of the joint by means of numerical simulation and data-driven methods. Thereby, a deeper understanding of the pin joining process is generated and the versatility of the novel joining process is increased. Additionally, the provision of manufacturing recommendations for the forming of pin joints leads to a significant decrease in the failure probability caused by ploughing or buckling effects.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Characterisation of Fibre Bundle Deformation Behaviour—Test Rig, Results and Conclusions - Borowski, Andreas; Gröger, Benjamin; Füßel, René; Gude, Maik (Journal of Manufacturing and Materials Processing)
Deformation of continuous fibre reinforced plastics during thermally-assisted forming or joining processes leads to a change of the initial material structure. The load behaviour of composite parts strongly depends on the resultant material structure. The prediction of this material structure is a challenging task and requires a deep knowledge of the material behaviour above melting temperature and the occurring complex forming phenomena. Through this knowledge, the optimisation of manufacturing parameters for a more efficient and reproducible process can be enabled and are in the focus of many investigations. In the present paper, a simplified pultrusion test rig is developed and presented to investigate the deformation behaviour of a thermoplastic semi-finished fiber product in a forming element. Therefore, different process parameters, like forming element temperature, pulling velocity as well as the forming element geometry, are varied. The deformation behaviour in the forming zone of the thermoplastic preimpregnated continuous glass fibre-reinforced material is investigated by computed tomography and the resultant pulling forces are measured. The results clearly show the correlation between the forming element temperature and the resulting forces due to a change in the viscosity of the thermoplastic matrix and the resulting fiber matrix interaction. In addition, the evaluation of the measurement data shows which forming forces are required to change the shape of the thermoplastic unidirectional material with a rectangular cross-section to a round one.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Pin Extrusion for Mechanical Joining from Orbital Formed Tailored Blanks with Local Material Pre-Distribution - Römisch, David; Hetzel, Andreas; Wituschek, Simon; Lechner, Michael; Merklein, Marion (Journal of Manufacturing and Materials Processing)
Pin extrusion is a common process to realise pin structures in different geometrical dimensions for a subsequent joining operation. Nevertheless, the process of pin extrusion offers process limits regarding sheet thinning as a consequence of the punch penetration depth into the sheet. Thereby, cracks at the residual sheet thickness can occur during strength tests, resulting in a failure of the complete joint due to severe thinning. Therefore, measures have to be taken into account to reduce the thinning. One possibility is the application of orbital formed tailored blanks with a local material pre-distribution, which allows a higher sheet thickness in the desired area. Within this contribution, the novel approach of a process combination of orbital forming and pin extrusion is investigated. To reveal the potential of a local material pre-distribution, conventional specimens are compared with previously orbital formed components. Relevant parameters such as the residual sheet thickness, the pin height as well as the average hardness values are compared. The results show a significant positive influence of a local material pre-distribution on the residual sheet thickness as well as the resulting pin height. Furthermore, the strain hardening during orbital forming can be seen as an additional advantage. To conclude the results, the process limits of conventional pin extrusion can be expanded significantly by the application of specimens with a local material pre-distribution.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Investigations on Combined in situ CT and Acoustic Analysis during Clinching - Köhler, Daniel; Stephan, Richard; Kupfer, Robert; Troschitz, Juliane; Brosius, Alexander; Gude, Maik (Key Engineering Materials)
Clinching is a cost efficient method for joining components in series production. To assure the clinch point’s quality, the force displacement curve during clinching or the bottom thickness are monitored. The most significant geometrical characteristics of the clinch point, neck thickness and undercut, are usually tested destructively by microsectioning. However, micrograph preparation goes ahead with a resetting of elastic deformations and crack-closing after unloading. To generate a comprehensive knowledge of the clinch point’s inner geometry under load, in-situ computed tomography (CT) and acoustic testing (TDA) can be combined. While the TDA is highly sensitive to the inner state of the clinch point, it could detect critical events like crack development during loading. If such events are indicated, the loading process is stopped and a stepped in-situ CT of the following crack and deformation development is performed. In this paper, the concept is applied to the process of clinching itself, providing a detailed three-dimensional insight in the development of the joining zone. A test set-up is used which allows a stepwise clinching of two aluminium sheets EN AW 6014. Furthermore, this set-up is positioned within a CT system. In order to minimize X-ray absorption, a beryllium cylinder is used within the set-up frame and clinching tools are made from Si3N4. The actuator and sensor necessary for the TDA are integrated in the set-up. In regular process steps, the clinching process is interrupted in order to perform a TDA and a CT scan. In order to enhance the visibility of the interface, a thin tin layer is positioned between the sheets prior clinching. It is shown, that the test-set up allows a monitoring of the dynamic behaviour of the specimen during clinching while the CT scans visualize the inner geometry and material flow non-destructively.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Numerical fatigue life prediction of corroded and non-corroded clinched joints - Harzheim, Sven; Hofmann, Martin; Wallmersperger, Thomas (Mechanics of Advanced Materials and Structures)
Mechanical clinching is used to create lightweight hybrid structures. In order to estimate the service life of clinched components, its fatigue properties need to be known under different mechanical loading conditions. In addition to fatigue, corrosion is another factor that affects the fatigue life of clinched joints. In the literature, many corrosion and high-cycle fatigue damage models exist. However, little is known about how both phenomena interact in clinched joints. In this article, the influence of galvanic corrosion on clinched EN AW-6014/HCT590X + Z sheets on the fatigue life is investigated by means of numerical simulations and experimental results. An accurate prediction of the Wöhler lines of non-corroded and pre-corroded clinched specimens is shown.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science; General Mathematics; Civil and Structural Engineering

Reproducibility and Scattering in Additive Manufacturing: Results from a Round Robin on PBF-LB/M AlSi10Mg Alloy - Schneider, M.; Bettge, D.; Binder, M.; Dollmeier, K.; Dreyer, Malte; Hilgenberg, K.; Klöden, B.; Schlingmann, T.; Schmidt, J. (Practical Metallography)
Abstract The round robin test investigated the reliability users can expect for AlSi10Mg additive manufactured specimens by laser powder bed fusion through examining powder quality, process parameter, microstructure defects, strength and fatigue. Besides for one outlier, expected static material properties could be found. Optical microstructure inspection was beneficial to determine true porosity and porosity types to explain the occurring scatter in properties. Fractographic analyses reveal that the fatigue crack propagation starts at the rough as-built surface for all specimens. Statistical analysis of the scatter in fatigue using statistical derived safety factors concludes that at a stress of 36.87 MPa the fatigue limit of 10 7 cycles could be reached for all specimen with a survival probability of 99.999 %.
Keywords: Metals and Alloys; Mechanics of Materials; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Size‐Dependent Strain Relaxation in InAs Quantum Dots on Top of GaAs(111)A Nanopillars - Riedl, Thomas; Kunnathully, Vinay; Trapp, Alexander; Langer, Timo; Reuter, Dirk; Lindner, Jörg (Advanced Materials Interfaces)
Keywords: Mechanical Engineering; Mechanics of Materials

Experimental and Numerical Investigation on Manufacturing-Induced Pre-Strain on the Load-Bearing Capacity of Clinched Joints - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson (Key Engineering Materials)
Background. Clinching is a conventional cold forming process in which two or more sheets can be joined without auxiliary parts. A pre-forming of the parts to be joined, which is introduced by previous manufacturing steps, has an influence on the joining result. When considering the suitability for joining with regard to the formability of the materials, the influence of the preforming steps must be taken into account. The influences of strain hardening and sheet thickness on the joining properties must be investigated. In this context, a Finite Element Method (FEM) based metamodel analysis of the clinching process was carried out in [1] to investigate the robustness of the clinching process with respect to the different material pre-strains. In [2], the method was extended to the load bearing simulation.Procedure. The metamodel from preliminary work based on various FE models, which predicts the load-bearing capacity of a clinched joint influenced by pre-straining, is compared here with experimental data and the accuracy of the metamodel prediction is discussed. For this purpose an experimental procedure was further develop which allows the preforming of metal sheets from which joining specimens can be separated with a certain degree of unidirectional deformation. In the study, the procedure for preparing the joint specimens and the results of the loading tests are presented. Different possible relevant pre-strain combinations are investigated and compared with the simulation results, to validate the FE models and choose suitable metamodel.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Functionality Study of an Optical Measurement Concept for Local Force Signal Determination in High Strain Rate Tensile Tests - Böhnke, Max; Unruh, Eduard; Sell, Stanislaw; Bobbert, Mathias; Hein, David; Meschut, Gerson (Key Engineering Materials)
Many mechanical material properties show a dependence on the strain rate, e.g. yield stress or elongation at fracture. The quantitative description of the material behavior under dynamic loading is of major importance for the evaluation of crash safety. This is carried out using numerical methods and requires characteristic values for the materials used. For the standardized determination of dynamic characteristic values in sheet metal materials, tensile tests performed according to the guideline from [1]. A particular challenge in dynamic tensile tests is the force measurement during the test. For this purpose, strain gauges are attached on each specimen, wired to the measuring equipment and calibrated. This is a common way to determine a force signal that is as low in vibration and as free of bending moments as possible. The preparation effort for the used strain gauges are enormous. For these reasons, an optical method to determine the force by strain measurement using DIC is presented. The experiments are carried out on a high speed tensile testing system. In combioantion with a 3D DIC high speed system for optical strain measurement. The elastic deformation of the specimen in the dynamometric section is measured using strain gauges and the optical method. The measured signals are then compared to validate the presented method. The investigations are conducted using the dual phase steel material HCT590X and the aluminum material EN AW-6014 T4. Strain rates of up to 240 s-1 are investigated.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Testing, modelling, and parameter identification for adhesively bonded joints under the influence of temperature - Schmelzle, Lars; Striewe, Marius; Mergheim, Julia; Meschut, Gerson; Possart, Gunnar; Teutenberg, Dominik; Hein, David; Steinmann, Paul (Journal of Adhesion Science and Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Mechanics of Materials; General Chemistry

Physics informed neural networks for continuum micromechanics - Henkes, Alexander; Wessels, Henning; Mahnken, Rolf (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

“Red Carbon”: A Rediscovered Covalent Crystalline Semiconductor - Odziomek, Mateusz; Giusto, Paolo; Kossmann, Janina; Tarakina, Nadezda V.; Heske, Julian; Rivadeneira, Salvador M.; Keil, Waldemar; Schmidt, Claudia; Mazzanti, Stefano; Savateev, Oleksandr; Perdigón‐Toro, Lorena; Neher, Dieter; et al. (Advanced Materials)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

C 1 N 1 Thin Films from Guanine Decomposition Fragments - Jerigová, Mária; Heske, Julian; Kühne, ThomasD.; Tian, Zhihong; Tovar, Michael; Odziomek, Mateusz; Lopez Salas, Nieves (Advanced Materials Interfaces)
Keywords: Mechanical Engineering; Mechanics of Materials

“Red Carbon”: A Rediscovered Covalent Crystalline Semiconductor - Odziomek, Mateusz; Giusto, Paolo; Kossmann, Janina; Tarakina, Nadezda V.; Heske, Julian Joachim; Rivadeneira, Salvador M.; Keil, Waldemar; Schmidt, Claudia; Mazzanti, Stefano; Savateev, Oleksandr; Perdigón‐Toro, Lorena; Neher, Dieter; et al. (Advanced Materials)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

The Structure of Water in Silica Mesopores – Influence of the Pore Wall Polarity - Weinberger, Christian; Zysk, Frederik; Hartmann, Marc; Kaliannan, Naveen; Keil, Waldemar; Kühne, Thomas; Tiemann, Michael (Advanced Materials Interfaces)
In the spatial confinement of cylindrical mesopores with diameters of a few nanometers, water molecules experience restrictions in hydrogen bonding. This leads to a different behavior regarding the molecular orientational freedom (‘structure of water') compared to the bulk liquid state. In addition to the pore size, the behavior is also strongly affected by the strength of the pore wall-to-water interactions, that is, the pore wall polarity. In this work, this is studied both experimentally and theoretically. The surface polarity of mesoporous silica (SiO2) is modified by functionalization with trimethylsilyl moieties, resulting in a change from a hydrophilic (pristine) to a hydrophobic pore wall. The mesopore surface is characterized by N2 and H2O sorption experiments. Those results are combined with IR spectroscopy to investigate pore wall-to-water interactions leading to different structures of water in the mesopore. Furthermore, the water's structure is studied theoretically to gain deeper insight into the interfacial interactions. For this purpose, the structure of water is analyzed by pairing densities, coordination, and angular distributions with a novel adaptation of surface-specific sum-frequency generation calculation for pore environments.
Keywords: Mechanical Engineering; Mechanics of Materials

Review on mechanical joining by plastic deformation - Meschut, Gerson; Merklein, M.; Brosius, A.; Drummer, D.; Fratini, L.; Füssel, U.; Gude, M.; Homberg, Werner; Martins, P.A.F.; Bobbert, Mathias; Lechner, M.; Kupfer, R.; et al. (Journal of Advanced Joining Processes)
Mechanical joining technologies are increasingly used in multi-material lightweight constructions and offer opportunities to create versatile joining processes due to their low heat input, robustness to metallurgical incompatibilities and various process variants. They can be categorised into technologies which require an auxiliary joining element, or do not require an auxiliary joining element. A typical example for a mechanical joining process with auxiliary joining element is self-piercing riveting. A wide range of processes exist which are not requiring an auxiliary joining element. This allows both point-shaped (e.g., by clinching) and line-shaped (e.g., friction stir welding) joints to be produced. In order to achieve versatile processes, challenges exist in particular in the creation of intervention possibilities in the process and the understanding and handling of materials that are difficult to join, such as fiber reinforced plastics (FRP) or high-strength metals. In addition, predictive capability is required, which in particular requires accurate process simulation. Finally, the processes must be measured non-destructively in order to generate control variables in the process or to investigate the cause-effect relationship. This paper covers the state of the art in scientific research concerning mechanical joining and discusses future challenges on the way to versatile mechanical joining processes.
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Review on mechanical joining by plastic deformation - Meschut, G.; Merklein, M.; Brosius, A.; Drummer, D.; Fratini, L.; Füssel, U.; Gude, M.; Homberg, W.; Martins, P.A.F.; Bobbert, M.; Lechner, M.; Kupfer, R.; et al. (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Further Development of an Adaptive Joining Technique Based on Friction Spinning to Produce Pre-Hole-Free Joints - Wischer, Christian; Homberg, Werner (Key Engineering Materials)
Mechanical joining processes are an essential part of modern lightweight construction. They permit materials of different types to be joined in a way that is suitable for the loads involved. These processes reach their limits, however, as soon as the boundary conditions change. In most cases, these elements are specially adapted to the joining point and cannot be used universally. Changes require cost-intensive adaptation of both the element and the process control, thus making production more complex. This results in high costs due to the increased number of auxiliary joining element variants required and reduces the economic efficiency of mechanical joining. One approach to overcoming this issue is the use of adaptive auxiliary joining elements formed by friction spinning. This article presents the current state of research on pre-hole-free joining with adaptive joining elements. The overall process chain is illustrated, explained and analyzed. Special attention is paid to demonstrating the feasibility of pre-hole-free joining with adaptive joining elements. The chosen mechanical parameters are subsequently listed. Finally, a comprehensive outlook of the future development potential is derived.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

A Review on the Modeling of the Clinching Process Chain - Part III: Operational Phase - Schramm, Britta; Harzheim, Sven; Weiß, Deborah; Joy, Tintu David; Hofmann, Martin; Mergheim, Julia; Wallmersperger, Thomas (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Development of a method for the separate measurement of the growth of internal crack tips by means of the potential drop method - Kullmer, Gunter; Weiß, Deborah; Schramm, Britta (Engineering Fracture Mechanics)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

NTFA-enabled goal-oriented adaptive space–time finite elements for micro-heterogeneous elastoplasticity problems - Ju, X.; Mahnken, Rolf; Xu, Y.; Liang, L. (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

New low order Runge–Kutta schemes for asymptotically exact global error estimation of embedded methods without order reduction - Mahnken, Rolf (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Manufacture of Defined Residual Stress Distributions in the Friction-Spinning Process: Driven Tool and Subsequent Flow-Forming - Dahms, Frederik; Homberg, Werner (Key Engineering Materials)
Friction-spinning as an innovative incremental forming process enables large degrees of deformation in the field of tube and sheet metal forming due to a self-induced heat generation in the forming zone. This paper presents a new tool and process design with a driven tool for the targeted adjustment of residual stress distributions in the friction-spinning process. Locally adapted residual stress depth distributions are intended to improve the functionality of the friction-spinning workpieces, e.g. by delaying failure or triggering it in a defined way. The new process designs with the driven tool and a subsequent flow-forming operation are investigated regarding the influence on the residual stress depth distributions compared to those of standard friction-spinning process. Residual stress depth distributions are measured with the incremental hole-drilling method. The workpieces (tubular part with a flange) are manufactured using heat-treatable 3.3206 (EN-AW 6060 T6) tubular profiles. It is shown that the residual stress depth distributions change significantly due to the new process designs, which offers new potentials for the targeted adjustment of residual stresses that serve to improve the workpiece properties.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Fracture mechanical evaluation of the material HCT590X - Schramm, Britta; Weiß, Deborah (Materials Testing)
For a reliable, strength-compliant and fracture-resistant design of components and technical structures and for the prevention of damage cases, both the criteria of strength calculation and fracture mechanics are essential. In contrast to strength calculation the fracture mechanics assumes the existence of cracks which might further propagate due to the operational load. First, the present paper illustrates the general procedure of a fracture mechanical evaluation of fatigue cracks in order to assess practical damage cases. Fracture mechanical fundamentals which are essential for the calculation of the stress intensity factors K I and the experimental determination of fracture mechanical material parameters (e.g. threshold Δ K I,th against fatigue crack growth, crack growth rate curve) are explained in detail. The subsequent fracture mechanical evaluation on the basis of the local stress situation at the crack tip and the fracture mechanical material data is executed for different materials and selected crack problems. Hereby, the main focus is on the material HCT590X as it is the essential material being investigated by TRR285.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Co-bonding of carbon fibre-reinforced epoxy and galvanised steel with laser structured interface for automotive applications - Voswinkel, Dietrich; Striewe, Jan Andre; Grydin, Olexandr; Meinderink, Dennis; Grundmeier, Guido; Schaper, Mirko; Tröster, Thomas (Advanced Composite Materials)
Keywords: Mechanical Engineering; Mechanics of Materials; Ceramics and Composites

Optical Detection of Phase Transformations in Steels: An Innovative Method for Time-Efficient Material Characterization During Tailored Thermo-mechanical Processing of a Press Hardening Steel - Reitz, Alexander; Grydin, Olexandr; Schaper, Mirko (Metallurgical and Materials Transactions A)
Abstract With an innovative optical characterization method, using high-temperature digital image correlation in combination with thermal imaging, the local change in strain and change in temperature could be determined during thermo-mechanical treatment of flat steel specimens. With data obtained by this optical method, the transformation kinetics for every area of interest along the whole measuring length of a flat specimen could be analyzed by the generation of dilatation curves. The benefit of this innovative optical characterization method compared to a dilatometer test is that the experimental effort for the design of a tailored component could be strongly reduced to the investigation of only a few tailored thermo-mechanical processed specimens. Due to the implementation of a strain and/or temperature gradient within the flat specimen, less metallographic samples are prepared for hardness analysis and analysis of the microstructural composition by scanning electron microscopy to investigate the influence of different process parameters. Compared to performed dilatometer tests in this study, the optical method obtained comparable results for the transformation start and end temperatures. For the final design of a part with tailored properties, the optical method is suitable for a time-efficient material characterization. Graphical Abstract
Keywords: Metals and Alloys; Mechanics of Materials; Condensed Matter Physics

The influence of surface on direction of diffusion in Al-Fe clad material - Šlapáková, Michaela; Křivská, Barbora; Fekete, Klaudia; Králík, Rostislav; Grydin, Olexandr; Stolbchenko, Mykhailo; Schaper, Mirko (Materials Characterization)
Aluminium-steel clad composite was manufactured by twin-roll casting. An intermetallic layer of Al5Fe2 and Al13Fe4 formed at the interface upon annealing above 500 °C. During in-situ annealing in transmission electron microscope, the layer grew towards the steel side of the interface in tongue-like protrusions. A study of furnace-annealed samples revealed, that the bulk growth of the interface phase proceeds towards the aluminium side. The growth towards steel is a surface effect that takes place simultaneously with the bulk growth towards aluminium. At the beginning of the intermetallic layer formation diffusion of Fe into aluminium prevails, afterwards Al atoms diffuse throught the newly formed intermetallic layer towards steel and the whole interface shifts towards aluminium. The kinetics of growth of the intermetallic layer follows parabolic law in both cases, indicating that the growth is governed by diffusion.
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Influence of thermomechanical processing on the microstructural and mechanical properties of steel 22MnB5 - Reitz, Alexander; Grydin, Olexandr; Schaper, Mirko (Materials Science and Engineering: A)
In order to reduce CO2 emissions in the transport sector, the approach of load-adapted components is increasingly being pursued. For the design of such components, it is crucial to determine their resulting microstructure and mechanical properties. For this purpose, continuous cooling transformation diagrams and deformation continuous cooling transformation diagrams are utilized, however, their curves are strongly influenced by the chemical composition, the initial state and especially the process parameters. In this study, the influence of the process parameters on the transformation kinetics is systematically investigated using an innovative characterization method. The experimental setup allowed a near-process analysis of the transformation kinetics, resulting microstructure and mechanical properties for a specific process route with a reduced number of specimens. A systematic investigation of the effects of different process parameters on the microstructural and mechanical properties made it possible to reveal interactions and independencies between the process parameters in order to design a partial heating or differential cooling process. Furthermore, the implementation of two different cooling conditions, representative of differential cooling in the die relief method with tool-contact and non-contact areas, showed that the soaking duration has a significant influence on the microstructure in the non-contact tool area.
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Tribo-functional PVD thin films deposited onto additively manufactured Ti6Al7Nb for biomedical applications - Tillmann, Wolfgang; Lopes Dias, Nelson Filipe; Kokalj, David; Stangier, Dominic; Hein, Maxwell; Hoyer, Kay-Peter; Schaper, Mirko; Gödecke, Daria; Oltmanns, Hilke; Meißner, Jessica (Materials Letters)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

On the influence of physical vapor deposited thin coatings on the low-cycle fatigue behavior of additively processed Ti-6Al-7Nb alloy - Hein, Maxwell; Lopes Dias, Nelson Filipe; Kokalj, David; Stangier, Dominic; Hoyer, Kay-Peter; Tillmann, Wolfgang; Schaper, Mirko (International Journal of Fatigue)
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials; General Materials Science; Modeling and Simulation

Additively manufactured novel Ti6Al7Nb circular honeycomb cellular solid for energy absorbing applications - Pramanik, Sudipta; Milaege, Dennis; Hoyer, Kay-Peter; Schaper, Mirko (Materials Science and Engineering: A)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Tribo-functional PVD thin films deposited onto additively manufactured Ti6Al7Nb for biomedical applications - Tillmann, Wolfgang; Lopes Dias, Nelson Filipe; Kokalj, David; Stangier, Dominic; Hein, Maxwell; Hoyer, Kay-Peter; Schaper, Mirko; Gödecke, Daria; Oltmanns, Hilke; Meißner, Jessica (Materials Letters)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Additively manufactured novel Ti6Al7Nb circular honeycomb cellular solid for energy absorbing applications - Pramanik, Sudipta; Milaege, Dennis; Hoyer, Kay-Peter; Schaper, Mirko (Materials Science and Engineering: A)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

On the influence of physical vapor deposited thin coatings on the low-cycle fatigue behavior of additively processed Ti-6Al-7Nb alloy - Hein, Maxwell; Lopes Dias, Nelson Filipe; Kokalj, David; Stangier, Dominic; Hoyer, Kay-Peter; Tillmann, Wolfgang; Schaper, Mirko (International Journal of Fatigue)
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials; General Materials Science; Modeling and Simulation

A Review on the Modeling of the Clinching Process Chain - Part I: Design Phase - Schramm, Britta; Martin, Sven; Steinfelder, Christian; Bielak, Christian Roman; Brosius, Alexander; Meschut, Gerson; Tröster, Thomas; Wallmersperger, Thomas; Mergheim, Julia (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

A Review on the Modeling of the Clinching Process Chain - Part II: Joining Process - Schramm, Britta; Friedlein, Johannes; Gröger, Benjamin; Bielak, Christian Roman; Bobbert, Mathias; Gude, Maik; Meschut, Gerson; Wallmersperger, Thomas; Mergheim, Julia (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Coupled microscopic and micromagnetic depth-specific analysis of plastic deformation and phase transformation of metastable austenitic steel AISI 304L by flow forming - Rozo Vasquez, Julian; Kanagarajah, Hanigah; Arian, Bahman; Kersting, Lukas; Homberg, Werner; Trächtler, Ansgar; Walther, Frank (Practical Metallography)
Abstract This paper presents the characterization of the microstructure evolution during flow forming of austenitic stainless steel AISI 304L. Due to plastic deformation of metastable austenitic steel, phase transformation from γ-austenite into α’-martensite occurs. This is initiated by the formation of shear bands as product of the external stresses. By means of coupled microscopic and micromagnetic investigations, a characterization of the microstructure was carried out. In particular, this study shows the distribution of the strain-induced α’-martensite and its influence on material properties like hardness at different depths. The microstructural analyses by means of electron backscattered diffraction (EBSD) technique, evidence a higher amount of α’-martensite (ca. 23 %) close to the outer specimen surface, where the plastic deformation and the direct contact with the forming tool take place. In the middle area (ca. 1.5 mm depth from the outer surface), the portion of transformed α’-martensite drops to 7 % and in the inner surface to 2 %. These results are well correlated with microhardness and micromagnetic measurements at different depths. EBSD and atomic force microscopy (AFM) were used to make a detailed characterization of the topography and degree of deformation of the shear bands. Likewise, the mechanisms of nucleation of α’-martensite were discussed. This research contributes to the development of micromagnetic sensors to monitor the evolution of properties during flow forming. This makes them more suitable for closed-loop property control, which offers possibilities for an application-oriented and more efficient production.
Keywords: Metals and Alloys; Mechanics of Materials; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Innovative Online Measurement and Modelling Approach for Property-Controlled Flow Forming Processes - Kersting, Lukas; Arian, Bahman; Vasquez, Julian Rozo; Trächtler, Ansgar; Homberg, Werner; Walther, Frank (Key Engineering Materials)
The production of complex multi-functional, high-strength parts is becoming increasingly important in the industry. Especially with small batch size, the incremental flow forming processes can be advantageous. The production of parts with complex geometry and locally graded material properties currently depicts a great challenge in the flow forming process. At this point, the usage of closed-loop control for the shape and properties could be a feasible new solution. The overall aim in this project is to establish an intelligent closed-loop control system for the wall thickness as well as the α’-martensite content of AISI 304L-workpieces in a flow forming process. To reach this goal, a novel sensor concept for online measurements of the wall thickness reduction and the martensite content during forming process is proposed. It includes the setup of a modified flow forming machine and the integration of the sensor system in the machine control. Additionally, a simulation model for the flow forming process is presented which describes the forming process with regard to the plastic workpiece deformation, the induced α’-martensite fraction, and the sensor behavior. This model was used for designing a closed-loop process control of the wall thickness reduction that was subsequently realized at the real plant including online measured feedback from the sensor system.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

In-Mold-Assembly of Hybrid Bending Structures by Compression Molding - Stallmeister, Tim; Tröster, Thomas (Key Engineering Materials)
The further development of in-mold-assembly (IMA) technologies for structural hybrid components is of great importance for increasing the economic efficiency and thus the application potential. This paper presents an innovative IMA process concept for the manufacturing of bending loaded hybrid components consisting of two outer metal belts and an inner core structure made of glass mat reinforced thermoplastic (GMT). In this process, the core structure, which is provided with stiffening ribs and functional elements, is formed and joined to two metal belts in one single step. For experimental validation of the concept, the development of a prototypic molding tool and the manufacturing of hybrid beams including process parameters are described. Three-point bending tests and optical measurement technologies are used to characterize the failure behavior and mechanical properties of the produced hybrid beams. It was found that the innovative IMA process enables the manufacturing of hybrid components with high energy absorption and low weight in one step. The mass-specific energy absorption is increased by 693 % compared to pure GMT beams.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Multichannel Superposition of Grafted Perfect Vortex Beams - Ahmed, Hammad; Intaravanne, Yuttana; Ming, Yang; Ansari, Muhammad Afnan; Buller, Gerald S.; Zentgraf, Thomas; Chen, Xianzhong (Advanced Materials)
Inspired by plant grafting, grafted vortex beams can be formed through grafting two or more helical phase profiles of optical vortex beams. Recently, grafted perfect vortex beams (GPVBs) have attracted much attention due to their unique optical properties and potential applications. However, the current method to generate and manipulate GPVBs requires a complex and bulky optical system, hindering further investigation and limiting its practical applications. Here, a compact metasurface approach for generating and manipulating GPVBs in multiple channels is proposed and demonstrated, which eliminates the need for such a complex optical setup. A single metasurface is utilized to realize various superpositions of GPVBs with different combinations of topological charges in four channels, leading to asymmetric singularity distributions. The positions of singularities in the superimposed beam can be further modulated by introducing an initial phase difference in the metasurface design. The work demonstrates a compact metasurface platform that performs a sophisticated optical task that is very challenging with conventional optics, opening opportunities for the investigation and applications of GPVBs in a wide range of emerging application areas, such as singular optics and quantum science.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

About the structure of the discrete and continuous Eringen’s nonlocal elastica - Cresson, Jacky; Hariz-Belgacem, Khaled (Mathematics and Mechanics of Solids)
The Eringen’s nonlocal elastica equation does not possess a Lagrangian formulation. In this article, we find a variational integrating factor which enables us to provide a Lagrangian and Hamiltonian structure associated to this equation. Explicit expressions of the solutions in terms of elliptic integrals of the first kind are then deduced. We then derive discrete version of the Eringen’s nonlocal elastica preserving the Lagrangian and Hamiltonian structure and compare it with Challamel’s and co-worker definition of a discrete Eringen’s nonlocal elastica.
Keywords: Mechanics of Materials; General Materials Science; General Mathematics

About the structure of the discrete and continuous Eringen’s nonlocal elastica - Cresson, Jacky; Hariz Belgacem, Khaled (Mathematics and Mechanics of Solids)
The Eringen’s nonlocal elastica equation does not possess a Lagrangian formulation. In this article, we find a variational integrating factor which enables us to provide a Lagrangian and Hamiltonian structure associated to this equation. Explicit expressions of the solutions in terms of elliptic integrals of the first kind are then deduced. We then derive discrete version of the Eringen’s nonlocal elastica preserving the Lagrangian and Hamiltonian structure and compare it with Challamel’s and co-worker definition of a discrete Eringen’s nonlocal elastica.
Keywords: Mechanics of Materials; General Materials Science; General Mathematics

Electrografting of BTSE: Zn films for advanced steel-aluminum joining by plastic deformation - Duderija, B.; González-Orive, A.; Schmidt, H.C.; Calderón, J.C.; Hordych, I.; Maier, H.J.; Homberg, W.; Grundmeier, G. (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Investigations on Combined In Situ CT and Acoustic Analysis during Clinching - Köhler, Daniel; Stephan, Richard; Kupfer, Robert; Troschitz, Juliane; Brosius, Alexander; Gude, Maik (Key Engineering Materials)
Clinching is a cost efficient method for joining components in series production. To assure the clinch point’s quality, the force displacement curve during clinching or the bottom thickness are monitored. The most significant geometrical characteristics of the clinch point, neck thickness and undercut, are usually tested destructively by microsectioning. However, micrograph preparation goes ahead with a resetting of elastic deformations and crack-closing after unloading. To generate a comprehensive knowledge of the clinch point’s inner geometry under load, in-situ computed tomography (CT) and acoustic testing (TDA) can be combined. While the TDA is highly sensitive to the inner state of the clinch point, it could detect critical events like crack development during loading. If such events are indicated, the loading process is stopped and a stepped in-situ CT of the following crack and deformation development is performed. In this paper, the concept is applied to the process of clinching itself, providing a detailed three-dimensional insight in the development of the joining zone. A test set-up is used which allows a stepwise clinching of two aluminium sheets EN AW 6014. Furthermore, this set-up is positioned within a CT system. In order to minimize X-ray absorption, a beryllium cylinder is used within the set-up frame and clinching tools are made from Si3N4. The actuator and sensor necessary for the TDA are integrated in the set-up. In regular process steps, the clinching process is interrupted in order to perform a TDA and a CT scan. In order to enhance the visibility of the interface, a thin tin layer is positioned between the sheets prior clinching. It is shown, that the test-set up allows a monitoring of the dynamic behaviour of the specimen during clinching while the CT scans visualize the inner geometry and material flow non-destructively.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Clinching of Aluminum Materials – Methods for the Continuous Characterization of Process, Microstructure and Properties - Kupfer, Robert; Köhler, Daniel; Römisch, David; Wituschek, Simon; Ewenz, Lars; Kalich, Jan; Weiß, Deborah; Sadeghian, Behdad; Busch, Matthias; Krüger, Jan; Neuser, Moritz; Grydin, Olexandr; et al. (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Clinching of Aluminum Materials – Methods for the Continuous Characterization of Process, Microstructure and Properties - Kupfer, Robert; Köhler, Daniel; Römisch, David; Wituschek, Simon; Ewenz, Lars; Kalich, Jan; Weiß, Deborah; Sadeghian, Behdad; Busch, Matthias; Krüger, Jan Tobias; Neuser, Moritz; Grydin, Olexandr; et al. (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

The Influence of Electrode Indentation Rate on LME Formation during RSW - Böhne, Christoph; Meschut, Gerson; BIEGLER, MAX; RETHMEIER, MICHAEL (Welding Journal)
During resistance spot welding of zinc-coated advanced high-strength steels (AHSSs) for automotive production, liquid metal embrittlement (LME) cracking may occur in the event of a combination of various unfavorable influences. In this study, the interactions of different welding current levels and weld times on the tendency for LME cracking in third-generation AHSSs were investigated. LME manifested itself as high-penetration cracks around the circumference of the spot welds for welding currents closely below the expulsion limit. At the same time, the observed tendency for LME cracking showed no direct correlation with the overall heat input of the investigated welding processes. To identify a reliable indicator of the tendency for LME cracking, the local strain rate at the origin of the observed cracks was analyzed over the course of the welding process via finite element simulation. While the local strain rate showed a good correlation with the process-specific LME cracking tendency, it was difficult to interpret due to its discontinuous course. Therefore, based on the experimental measurement of electrode displacement during welding, electrode indentation velocity was proposed as a descriptive indicator for quantifying cracking tendency.
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Clinching of Aluminum Materials – Methods for the Continuous Characterization of Process, Microstructure and Properties - Kupfer, Robert; Köhler, Daniel; Römisch, David; Wituschek, Simon; Ewenz, Lars; Kalich, Jan; Weiß, Deborah; Sadeghian, Behdad; Busch, Matthias; Krüger, Jan Tobias; Neuser, Moritz; Grydin, Olexandr; et al. (Journal of Advanced Joining Processes)
Clinching as a mechanical joining technique allows a fast and reliable joining of metal sheets in large-scale production. An efficient design and dimensioning of clinched joints requires a holistic understanding of the material, the joining process and the resulting properties of the joint. In this paper, the process chain for clinching metal sheets is described and experimental techniques are proposed to analyze the process-microstructure-property relationships from the sheet metal to the joined structure. At the example of clinching aluminum EN AW 6014, characterization methods are applied and discussed for the following characteristics: the mechanical properties of the sheet materials, the tribological behavior in the joining system, the joining process and the resulting material structure, the load-bearing behavior of the joint, the damage and degradation as well as the service life and crack growth behavior. The compilation of the characterization methods gives an overview on the advantages and weaknesses of the methods and the multiple interactions of material, process and properties during clinching. In addition, the results of the analyses on EN AW 6014 can be applied for parameterization and validation of simulations.
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Insights into the decomposition of zirconium acetylacetonate using synchrotron radiation: Routes to the formation of volatile Zr-intermediates - Grimm, Sebastian; Baik, Seung-Jin; Hemberger, Patrick; Kasper, Tina; Kempf, Andreas M.; Atakan, Burak (Journal of Materials Research)
Abstract The thermal decomposition of Zr(acac) 4 is studied in a SiC-microreactor on the micro-second time scale. By utilizing synchrotron radiation and photoelectron photoion coincidence spectroscopy, six important zirconium intermediates, as for instance Zr(C 5 H 7 O 2 ) 2 (C 5 H 6 O 2 ), and Zr(C 5 H 6 O 2 ) 2 , are identified in the gas phase for the first time. The adiabatic ionization thresholds of intermediately formed zirconium species are estimated and the main products of their thermal decomposition, acetylacetone, acetylallene and acetone are characterized unambiguously and isomer-selectively. Based on all detected intermediates, we deduce the predominant pyrolysis pathways of the precursor in the temperature range from 400 to 900 K. Our findings are complemented by numerical simulations of the flow field in the microreactor, which show that the choice of dilution gas significantly influences the temperature profile and residence times in the microreactor, such that helium provides a more uniform flow field than argon and should preferentially be used. Graphical abstract Using a soft ionization method coupled to velocity map imaging (VMI), leads to valuable insights in the thermal decomposition of Zr(C 5 H 7 O 2 ) 4 , used in the synthesis of functional nanomaterials and ceramic coatings. Thanks to the use of a microreactor, important gas
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Mechanism and Kinetics of the Thermal Decomposition of Fe(C5H5)2 in Inert and Reductive Atmosphere: A Synchrotron‐Assisted Investigation in A Microreactor - Grimm, Sebastian; Hemberger, Patrick; Kasper, Tina; Atakan, Burak (Advanced Materials Interfaces)
Abstract The decomposition and reduction of ferrocene, an important precursor for iron chemical vapor deposition and catalyst for nanotube synthesis, is investigated in the gas‐phase. Reactive intermediates are detected to understand the underlying chemistry by using a microreactor coupled to a synchrotron light source. Utilizing soft photoionization coupled with photoelectron‐photoion coincidence detection enables us to characterize exclusive intermediates isomer‐selectively. A reaction mechanism for the ferrocene decomposition is proposed, which proceeds as a two‐step process. Initially, the molecule decomposes in a homogeneous surface reaction at temperatures <900 K, leading to products such as cyclopentadiene and cyclopentadienyl radicals that are immediately released to the gas‐phase. At higher temperatures, ferrocene rapidly decomposes in the gas‐phase, losing two cyclopentadienyl radicals in conjunction with iron. The addition of hydrogen to the reaction mixture reduces the decomposition temperature, and changes the branching ratio of the products. This change is mainly attributed to the H‐addition of cyclopentadienyl radicals on the surface, which leads to a release of cyclopentadiene into the gas‐phase. On the surface, ligand fragments may also undergo a series of catalytic H‐losses leading most probably to a high carbon content in the film. Finally, Arrhenius parameters for both global reactions are presented.
Keywords: Mechanical Engineering; Mechanics of Materials

Stimulation and Enhancement of Near‐Band‐Edge Emission in Zinc Oxide by Distributed Bragg Reflectors - Kothe, Linda; Albert, Maximilian; Meier, Cedrik; Wagner, Thorsten; Tiemann, Michael (Advanced Materials Interfaces)
The free exciton transition (near-band-edge emission, NBE) of ZnO at ≈388 nm can be strongly enhanced and even stimulated by an underlying photonic structure. 1D Photonic crystals, so-called distributed Bragg reflectors, are utilized to suppress the deep-level emission of ZnO (DLE, ≈500–530 nm). The reflector stacks are fabricated in a layer-by-layer procedure by wet-chemical synthesis. They consist of low-ε porous SiO2 layers and high-ε TiO2 layers. Varying the thickness of the SiO2 layers allows tuning the optical bandgap in a wide range between ≈420 and 800 nm. A ZnO layer is deposited on top of the reflector stacks by sol–gel synthesis. The spontaneous photoluminescence (PL) emission of the ZnO film is modulated by the photonic structure. When the optical bandgap of the reflector is in resonance with the deep-level emission of ZnO (DLE, ≈500–530 nm), then this defect-related emission mode is suppressed. Strong NBE emission is observed even when the ZnO layer does not show any NBE emission (due to low crystallinity) in the absence of the photonic structure. With this cost-efficient synthesis method, emitters for, e.g., luminescent gas sensors can be fabricated.
Keywords: Mechanical Engineering; Mechanics of Materials

An automated approach for developing neural network interatomic potentials with FLAME - Mirhosseini, Hossein; Tahmasbi, Hossein; Kuchana, Sai Ram; Ghasemi, Alireza; Kühne, Thomas (Computational Materials Science)
Keywords: Computational Mathematics; General Physics and Astronomy; Mechanics of Materials; General Materials Science; General Chemistry; General Computer Science

Development of a Method for the Identification of Friction Coefficients in Sheet Metal Materials for the Numerical Simulation of Clinching Processes - Rossel, Moritz Sebastian; Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (Key Engineering Materials)
In order to reduce the fuel consumption and consequently the greenhouse emissions, the automotive industry is implementing lightweight constructions in the body in white production. As a result, the use of aluminum alloys is continuously increasing. Due to poor weldability of aluminum in combination with other materials, mechanical joining technologies like clinching are increasingly used. In order to predict relevant characteristics of clinched joints and to ensure the reliability of the process, it is simulated numerically during product development processes. In this regard the predictive accuracy of the simulated process highly depends on the implemented friction model. In particular, the frictional behavior between the sheet metals affects the geometrical formation of the clinched joint significantly. This paper presents a testing method, which enables to determine the frictional coefficients between sheet metal materials for the simulation of clinching processes. For this purpose, the correlation of interface pressure and the relative velocity between aluminum sheets in clinching processes is investigated using numerical simulation. Furthermore, the developed testing method focuses on the specimen geometry as well as the reproduction of the occurring friction conditions between two sheet metal materials in clinching processes. Based on a methodical approach the test setup is explained and the functionality of the method is proven by experimental tests using sheet metal material EN AW6014.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Numerical and Experimental Fracture Mechanical Investigations of Clinchable Sheet Metals Made of HCT590X - Weiß, Deborah; Schramm, Britta; Kullmer, Gunter (Key Engineering Materials)
In many areas of product manufacturing constructions consist of individual components and metal sheets that are joined together to form complex structures. A simple and industrial common method for joining dissimilar and coated materials is clinching. During the joining process and due to the service load cracks can occur in the area of the joint, propagate due to cyclic loading and consequently lead to structural failure. For the prevention of these damage cases, first of all knowledge about the fracture mechanical material parameters regarding the original material state of the sheet metals used within the clinching process are essential.Within the scope of this paper experimental and numerical preliminary investigations regarding the fracture mechanical behavior of sheet metals used within the clinching process are presented. Due to the low thickness of 1.5 mm of the material sheets, the development of a new specimen is necessary to determine the crack growth rate curve including the fracture mechanical parameters like the threshold against crack growth ΔK I,th and the fracture toughness K IC of the base material HCT590X. For the experimental determination of the crack growth rate curve the numerical calculation of the geometry factor function as well as the calibration function of this special specimen are essential. After the experimental validation of the numerically determined calibration function, crack growth rate curves are determined for the stress ratios R = 0.1 and R = 0.3 to examine the mean stress sensitivity. In addition, the different rolling directions of 0° and 90° in relation to the initial crack are taken into account in order to investigate the influence of the anisotropy due to rolling.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Atomically Thin Sheets of Lead‐Free 1D Hybrid Perovskites Feature Tunable White‐Light Emission from Self‐Trapped Excitons - Klement, Philip; Dehnhardt, Natalie; Dong, Chuan-Ding; Dobener, Florian; Bayliff, Samuel; Winkler, Julius; Hofmann, Detlev M.; Klar, Peter J.; Schumacher, Stefan; Chatterjee, Sangam; Heine, Johanna (Advanced Materials)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

New Approach for Versatile Self Piercing Riveting: Joining System and Auxiliary Part - Kappe, Fabian; Bobbert, Mathias; Meschut, Gerson (Key Engineering Materials)
The increasing use of multi-material constructions lead to a continuous increase in the use of mechanical joining techniques due to the wide range of joining possibilities as well as the high load-bearing capacities of the joints. Nevertheless, the currently rigid tool systems are not able to react to changing boundary conditions, like changing the material-geometry-combination. Therefore research work is crucial with regard to versatile joining systems. In this paper, a new approach for a versatile self-piercing riveting process considering the joining system as well as the auxiliary joining part is presented.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Strength enhancement of AlMg sheet metal parts by rapid heating and subsequent cold die stamping of severely cold-rolled blanks - Camberg, Alan Adam; Andreiev, Anatolii; Pramanik, Sudipta; Hoyer, Kay-Peter; Tröster, Thomas; Schaper, Mirko (Materials Science and Engineering: A)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Additively processed TiAl6Nb7 alloy for biomedical applications - Hein, Maxwell; Hoyer, Kay-Peter; Schaper, Mirko (Materialwissenschaft und Werkstofftechnik)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Laser beam melting of functionally graded materials with application-adapted tailoring of magnetic and mechanical performance - Andreiev, Anatolii; Hoyer, Kay-Peter; Dula, Dimitri; Hengsbach, Florian; Grydin, Olexandr; Frolov, Yaroslav; Schaper, Mirko (Materials Science and Engineering: A)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Quasi in-situ analysis of fracture path during cyclic loading of double-edged U notched additively manufactured FeCo alloy - Pramanik, Sudipta; Andreiev, Anatolii; Hoyer, Kay-Peter; Schaper, Mirko (International Journal of Fatigue)
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials; General Materials Science; Modeling and Simulation

Bioresorbable AgCe and AgCeLa alloys for adapted Fe-based implants - Krüger, Jan Tobias; Hoyer, Kay-Peter; Schaper, Mirko (Materials Letters)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Correlation between Taylor Model Prediction and Transmission Electron Microscopy-Based Microstructural Investigations of Quasi-In Situ Tensile Deformation of Additively Manufactured FeCo Alloy - Pramanik, Sudipta; Tasche, Lennart; Hoyer, Kay-Peter; Schaper, Mirko (Journal of Materials Engineering and Performance)
Abstract Within this research, the multiscale microstructural evolution before and after the tensile test of a FeCo alloy is addressed. X-ray µ -computer tomography (CT), electron backscattered diffraction (EBSD), and transmission electron microscopy (TEM) are employed to determine the microstructure on different length scales. Microstructural evolution is studied by performing EBSD of the same area before and after the tensile test. As a result, $$\langle$$ ⟨ 001 $$\rangle$$ ⟩ ||TD, $$\langle$$ ⟨ 011 $$\rangle$$ ⟩ ||TD are hard orientations and $$\langle$$ ⟨ 111 $$\rangle$$ ⟩ ||TD is soft orientations for deformation accommodation. It is not possible to predict the deformation of a single grain with the Taylor model. However, the Taylor model accurately predicts the orientation of all grains after deformation. {123} $$\langle$$ ⟨ 111 $$\rangle$$ ⟩ is the most active slip system, and {112} $$\langle$$ ⟨ 111 $$\rangle$$ ⟩ is the least active slip system. Both EBSD micrographs show grain subdivision after tensile testing. TEM images show the formation of dislocation cells. Correlative HRTEM images show unresolved lattice fringes at dislocation cell boundaries, whereas resolved lattice fringes are observed at dislocation cell interior. Since Schmid’s law is unable to predict the deformation behavior of grains, the boundary slip transmission accurately predicts the grain deformation behavior.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Novel AgCa and AgCaLa alloys for Fe-based bioresorbable implants with adapted degradation - Krüger, Jan Tobias; Hoyer, Kay-Peter; Filor, Viviane; Pramanik, Sudipta; Kietzmann, Manfred; Meißner, Jessica; Schaper, Mirko (Journal of Alloys and Compounds)
Keywords: Materials Chemistry; Metals and Alloys; Mechanical Engineering; Mechanics of Materials

A Method for Characterization of Geometric Deviations in Clinch Points with Computed Tomography and Transient Dynamic Analysis - Köhler, Daniel; Sadeghian, Behdad; Kupfer, Robert; Troschitz, Juliane; Gude, Maik; Brosius, Alexander (Key Engineering Materials)
When joining lightweight parts of various materials, clinching is a cost efficient solution. In a production line, the quality of a clinch point is primarily controlled by measurement of dimensions, which are accessible from outside. However, methods such as visual testing and measuring the bottom thickness as well as the outer diameter are not able to deliver any information about the most significant geometrical characteristic of the clinch point, neck thickness and undercut. Furthermore, ex-situ destructive methods such as microsectioning cannot detect elastic deformations and cracks that close after unloading. In order to exceed the current limits, a new non-destructive in-situ testing method for the clinching process is necessary. This work proposes a concept to characterize clinch points in-situ by combining two complementary non-destructive methods, namely, computed tomography (CT) and ultrasonic testing. Firstly, clinch points with different geometrical characteristics are analysed experimentally using ex-situ CT to get a highly spatially resolved 3D-image of the object. In this context, highly X-ray attenuating materials enhancing the visibility of the sheet-sheet interface are investigated. Secondly, the test specimens are modelled using finite element method (FEM) and a transient dynamic analysis (TDA) is conducted to study the effect of the geometrical differences on the deformation energy and to qualify the TDA as a fast in-situ non-destructive method for characterizing clinch points at high temporal resolution.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Characterisation of lateral offsets in clinch points with computed tomography and transient dynamic analysis - Köhler, D.; Sadeghian, B.; Troschitz, J.; Kupfer, R.; Gude, M.; Brosius, A. (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

High cycle life all-solid-state fluoride ion battery with La 2 NiO 4+d high voltage cathode - Nowroozi, Mohammad Ali; Wissel, Kerstin; Donzelli, Manuel; Hosseinpourkahvaz, Niloofar; Plana-Ruiz, Sergi; Kolb, Ute; Schoch, Roland; Bauer, Matthias; Malik, Ali Muhammad; Rohrer, Jochen; Ivlev, Sergei; Kraus, Florian; et al. (Communications Materials)
Abstract Fluoride ion batteries (FIBs) are a recent alternative all-solid-state battery technology. However, the FIB systems proposed so far suffer from poor cycling performance. In this work, we report La 2 NiO 4.13 with a Ruddlesden-Popper type structure as an intercalation-based active cathode material in all solid-state FIB with excellent cycling performance. The critical charging conditions to maintain the conductivity of the cell were determined, which seems to be a major obstacle towards improving the cycling stability of FIBs. For optimized operating conditions, a cycle life of about 60 cycles and over 220 cycles for critical cut-off capacities of 50 mAh/g and 30 mAh/g, respectively, could be achieved, with average Coulombic efficiencies between 95 – 99%. Cycling of the cell is a result of fluorination/de-fluorination into and from the La 2 NiO 4+d cathode, and it is revealed that La 2 NiO 4.13 is a multivalent electrode material. Our findings suggest that La 2 NiO 4.13 is a promising high energy cathode for FIBs.
Keywords: Mechanics of Materials; General Materials Science

Refill friction stir spot and resistance spot welding of aluminium joints with large total sheet thicknesses (III-1965-19) - Schmal, Christopher; Meschut, Gerson (Welding in the World)
Refill friction stir spot welding (RFSSW) is a highly flexible and promising solid-state joining method for aluminium alloys. Alternatively, resistance spot welding (RSW) can be stated as an appropriate joining method which can be automated and used within a high-volume production due to short process times. Both processes do not need any additional elements and a flat surface on both sides of the joints can be realised. In order to meet the modern requirements for crash safety and structural stiffness, thermal and mechanical joining methods are mainly combined by using single-component epoxy resin adhesives. Due to an insufficient knowledge about the application of both thermal joining methods for the abovementioned material combinations combined with additional adhesives, deeper investigations were done regarding the interactions of the polymers and the joining processes. Starting with a brief presentation of the boundary conditions of the investigations and the refill friction stir spot welding and resistance spot welding of high-strength aluminium alloys with sheet thicknesses bigger than 5.8 mm, the paper introduces the process-related joint properties of friction-based and resistance-based welded joints. Afterwards, the paper discusses the influences of the process parameter on the metallographic joint formation and load-bearing capacities for a selected two-sheet and four-sheet material combination. When combining the spot welding technologies with adhesives, the process parameters of the RFSSW process have to be adapted for the two-sheet combination by adding a squeeze-out step, while for RSW, just the preholding time has to be increased. Different challenges for both joining methods are shown. For RFSSW, the gap formation has to be considered when welding big total sheet thicknesses, while for RSW, the shape of the weld nugget is more important for an appropriate joint performance. Additionally, process optimisations for less adhesive incineration will be discussed for both joining processes, and the influences of the adhesive on the joint formation will be addressed with the help of load-bearing capacity evaluations. The paper closes with specific recommendations for the realisation of refill friction stir and resistance spot-welded joints with and without adhesive in the field of Al joints with big total sheet thicknesses which meet the quality demands and an outlook for further research steps will be given.
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Early stage crack detection in mechanically joined steel/aluminum joints by condition monitoring - Gollnick, Maik; Giese, Patrick; Hein, David; Meschut, Gerson; Herfert, Daniel (Materials Testing)
Monitoring systems for machines, plants, materials and equipment are increasingly used in production processes. These online condition monitoring systems can detect damage or excessive loads at an early stage and can drastically reduce or prevent long downtimes of plants and machines as well as high repair and maintenance costs. This paper depicts a method for online crack detection with pattern recognition methods for specimens joined by self-pierce riveting under cyclic load in fatigue tests (laboratory application). A software specially conceived for this application was developed. This software, AnrissMF, uses active acoustic testing with a structure-borne sensor to detect cracks in the joints at a very early stage. It is shown in this paper that this software can detect cracks much earlier than classical failure criteria for joints (i. e. before any drop in stiffness or frequency is observed). Furthermore, the successful application of software AnrissMF for online crack detection during the fatigue strength test is presented.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Process characteristics and influences of production-related disturbances in resistance element welding of hybrid materials with steel cover sheets and polymer core - Schmal, Christopher; Meschut, Gerson (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Effect of substrate pre‐treatment on the low cycle fatigue performance of tungsten carbide‐cobalt coated additive manufactured 316 L substrates - Tillmann, Wolfgang; Hagen, Leif; Garthe, Kai-Uwe; Hoyer, Kay-Peter; Schaper, Mirko (Materialwissenschaft und Werkstofftechnik)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Characterization of the fatigue behaviour for SAE 1045 steel without and with load-free sequences based on non-destructive, X-ray diffraction and transmission electron microscopic investigations - Wu, Haoran; Bill, T.; Teng, Z.J.; Pramanik, Sudipta; Hoyer, Kay-Peter; Schaper, Mirko; Starke, Peter (Materials Science and Engineering: A)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Degradable silver‐based alloys - Andreiev, Anatolii; Hoyer, Kay-Peter; Grydin, Olexandr; Frolov, Yaroslav; Schaper, Mirko (Materialwissenschaft und Werkstofftechnik)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Clinching in in-situ CT—A numerical study on suitable tool materials - Köhler, Daniel; Kupfer, Robert; Gude, Maik (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Joining of high strength aluminum alloys by refill friction stir spot welding (III-1854-18) - Schmal, Christopher; Meschut, Gerson; Buhl, Nico (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Joining of blanks by cold pressure welding: Incremental rolling and strategies for surface activation and heat treatment - Schmidt, H.C.; Homberg, W.; Orive, A.G.; Grundmeier, G.; Duderija, B.; Hordych, I.; Herbst, S.; Nürnberger, F.; Maier, H.J. (Materialwissenschaft und Werkstofftechnik)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Nano-architectural complexity of zinc oxide nanowall hollow microspheres and their structural properties - Engelkemeier, Katja; Lindner, Jörg K N; Bürger, Julius; Vaupel, Kathrin; Hartmann, Marc; Tiemann, Michael; Hoyer, Kay-Peter; Schaper, Mirko (Nanotechnology)
Keywords: Electrical and Electronic Engineering; Mechanical Engineering; Mechanics of Materials; General Materials Science; General Chemistry; Bioengineering

Joining of blanks by cold pressure welding: Incremental rolling and strategies for surface activation and heat treatment - Schmidt, H.C.; Homberg, W.; Orive, A.G.; Grundmeier, G.; Duderija, B.; Hordych, I.; Herbst, S.; Nürnberger, F.; Maier, H.J. (Materialwissenschaft und Werkstofftechnik)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Adjusting the Structure and Electronic Properties of Carbons for Metal‐Free Carbocatalysis of Organic Transformations - Antonietti, Markus; Lopez Salas, Nieves; Primo, Ana (Advanced Materials)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Influence of sp3/sp2-carbon ratio of vertically standing carbon nanostructures produced by pulsed laser-treatment on PAN-based carbon fibers - Engelkemeier, Katja; Hoyer, Kay-Peter; Schaper, Mirko (Materials Letters)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Mimicking synaptic plasticity and learning behaviours in solution processed SnO2 memristor - Pan, Ying; Wan, Tao; Du, Haiwei; Qu, Bo; Wang, Danyang; Ha, Tae-Jun; Chu, Dewei (Journal of Alloys and Compounds)
Keywords: Materials Chemistry; Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Process characteristics and load-bearing capacities of joints welded with elements for the application in multi-material design - Meschut, Gerson; Schmal, Christopher; Olfermann, Thomas (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Self-locking self-pierce riveting: a new self-pierce riveting technology for multi-material applications in lightweight car body structures - Sartisson, Vadim; Meschut, Gerson (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Combining a high-speed mechanical joining technique with the attachment of functional elements in automotive structures - Nagel, Philipp; Meschut, Gerson (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Flow drill screwing of fibre-reinforced plastic-metal composites without a pilot hole - Nagel, Philipp; Meschut, Gerson (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Corrosion properties of bioresorbable FeMn-Ag alloys prepared by selective laser melting - Wiesener, Markus; Peters, K.; Taube, Alexander; Keller, Adrian; Hoyer, Kay-Peter; Niendorf, Thomas; Grundmeier, Guido (Materials and Corrosion)
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry; Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry; Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry

Duplex stainless steel fabricated by selective laser melting - Microstructural and mechanical properties - Hengsbach, Florian; Koppa, Peter; Duschik, Kristina; Holzweissig, Martin Joachim; Burns, Madison; Nellesen, Jens; Tillmann, Wolfgang; Tröster, Thomas; Hoyer, Kay-Peter; Schaper, Mirko (Materials & Design)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Mechanical properties of an innovative shear-clinching technology for ultra-high-strength steel and aluminium in lightweight car body structures - Hörhold, Réjane; Müller, Martin; Merklein, Marion; Meschut, Gerson (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Investigation on joint characteristics of laser beam welded press hardenable ultra-high strength steels with ferritic-martensitic and martensitic microstructure - Janzen, V.; Meschut, G.; Dahmen, M.; Poprawe, R.; Lindner, S.; Wagener, R.; Melz, T. (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Development of a Testing Method for the Identification of Friction Coefficients for Numerical Modeling of the Shear-Clinching Process - Müller, Martin; Vierzigmann, Ulrich; Hörhold, Réjane; Meschut, Gerson; Merklein, Marion (Key Engineering Materials)
Global competition as well as social and scientific megatrends strongly influence the modern car manufacturing industry. One of the most important approaches is the implementation of lightweight constructions. Therefore, the usage of high performance materials with tailored properties gains importance. For safety-relevant components such as automotive passenger cells it is necessary to minimize deformation to reduce the risk of injury for the vehicle occupants during a car accident. Thus, hot stamped high-strength steels have been established. High-strength and low formability of this kind of materials represent new challenges for joining technologies. One possibility to join high-strength steels is the newly developed shear-clinching technology. Due to the use of a combined cutting and joining process, the connection of dissimilar materials with high difference in strength and formability can be achieved. Further research to ensure process reliability and to improve the strength of the joint is required. One possible approach for this is the numerical investigation of the material flow during the joining process. Therefore, the definition of process parameters for the finite element model is necessary. A big impact on the quality of the results has the accuracy of the used friction values. As established testing methods are not suitable for modeling the rather complex tribological system between the joining partners of the shear-clinching process, an innovative testing method is needed. Studies in the field of sheet-bulk metal forming already demonstrated the applicability of the ring compression test for sheet metals. This paper presents a concept for the adaption of the ring compression test to the specific needs of the investigated shear-clinching process. The numerical identification of the friction coefficients is validated by experimental data and first results are qualified by experimental and simulative shear-clinching joints.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Processing of New Materials by Additive Manufacturing: Iron-Based Alloys Containing Silver for Biomedical Applications - Niendorf, Thomas; Brenne, Florian; Hoyer, Kay-Peter; Schwarze, Dieter; Schaper, Mirko; Grothe, Richard; Wiesener, Markus; Grundmeier, Guido; Maier, Hans Jürgen (Metallurgical and Materials Transactions A)
Keywords: Metals and Alloys; Mechanics of Materials; Condensed Matter Physics

A series of amide functionalized isoreticular metal organic frameworks - Keceli, E.; Hemgesberg, M.; Grünker, R.; Bon, V.; Wilhelm, C.; Philippi, T.; Schoch, Roland; Sun, Y.; Bauer, Matthias; Ernst, S.; Kaskel, S.; Thiel, Werner R. (Microporous and Mesoporous Materials)
Keywords: Mechanics of Materials; Condensed Matter Physics; General Materials Science; General Chemistry

The use of radiation-cured adhesives on adhesive stud assembly process - Meschut, Gerson; Süllentrop, Sebastian (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Innovative and Highly Productive Joining Technologies for Multi-Material Lightweight Car Body Structures - Meschut, G.; Janzen, V.; Olfermann, T. (Journal of Materials Engineering and Performance)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Basic Investigations of Non-Pre-Punched Joining by Forming of Aluminium Alloy and High Strength Steel with Shear-Clinching Technology - Merklein, Marion; Meschut, Gerson; Müller, Martin; Hörhold, Réjane (Key Engineering Materials)
Facing a decreasing amount of resources on the one hand and an increasing demand for comfort on the other, more and more attention is being paid to sustainability and care for the environment. Particularly in the automotive sector, lightweight design principles continue to prosper rapidly. As a result, adjusted materials for different applications were developed. Due to the formation of intermetallic phases, most multi-material mixes cannot be welded and require adapted joining technologies. Mechanical joining technologies such as self-piercing riveting and mechanical clinching have proven effective methods of joining lightweight materials like aluminium and ductile steels. New high-strength steels are increasingly used in crash-sections, where limited deformation under impact load is required. These hot stamped steels have a very low elongation at break and therefore a low formability. Currently there is no joining by forming technology without pre-punching available using these grades of steels on die-side. The newly developed shear-clinching process is one possible method of joining this kind of material without additional elements. The fundamental idea of shear-clinching is a single-stage process in which pre-punching of the die-side material is performed by indirect shear-cutting and subsequent forming of the upper layer into this hole. This would immensely enlarge the application segment of mechanical clinching even if hot stamped steels are positioned on die-side. Fundamental studies are required to ensure process reliability and it is necessary to break down the joining process into fragments, like pre-punching and clinching with pre-punched sheet, and superpose them to form the combined procedure shear-clinching. This paper presents a detailed investigation of the sub-process clinching with pre-hole.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Innovative joining technologies for multi-material structures - Meschut, G.; Hahn, O.; Janzen, V.; Olfermann, T. (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Korrosionsverhalten binärer Magnesium-Zink-Legierungen in salzhaltigen Medien - Hoyer, Kay-Peter; Angrisani, Gian Luigi; Klose, Christian; Bach, Friedrich-Wilhelm; Hassel, Thomas (Materialwissenschaft und Werkstofftechnik)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science